El Ensayo Político de Humboldt sobre Cuba: presencia y ausencia de pensamientos habaneros sobre esclavitud y ciencia (1801-1826) - Misas Jiménez, Rolando E. (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2009)
Abstract The Political Essay on the island of Cuba by Humboldt is an important study on the thought of the landholders and colonial functionaries from Havana, who were his principal collaborators during the period 1801-1826. According to his ideas of human progress, Humboldt criticized the influence of the thought, based on the exploitation of slave labour, in the scientific, social and economical problems of the island. Therefore, Humboldt was worried about the political aspirations of the landholders. However, he almost didn´t address the reformist program carried out by Intendant Alejandro Ramírez. On the other hand, Humboldt ignored the progress thought of a group of professors and students from San Carlos´s College Seminary in Havana. His first contacts with this thought happened in Europe after his Essay having been published in 1826. Resumen El Ensayo Político sobre la isla de Cuba de Humboldt constituye un importante estudio sobre el pensamiento de los hacendados y de los funcionarios coloniales de La Habana, quienes fueron sus principales colaboradores durante el período 1801-1826. En correspondencia con sus ideas de progreso humano, Humboldt criticó la influencia del pensamiento, basado en la explotación de la fuerza de trabajo esclava, en los problemas de carácter científico, social y económico de la Isla. Por eso Humboldt se preocupó por las aspiraciones políticas de los hacendados. Sin embargo, casi no señala el programa reformista efectuado por el Intendente Alejandro Ramírez. Por otra parte, Humboldt desconoció el pensamiento de progreso de un grupo de profesores y estudiantes del Colegio Seminario de San Carlos en La Habana. Sus primeros contactos con este pensamiento ocurrieron en Europa después de haberse publicado su Ensayo en 1826.